Viscosity Of Aqueous Solutions Of NMethyldiethanolamine + Monoethanolamine (MDEA+MEA) - Arachchige, U.S. P. R. (INTERNATIONAL JOURNAL OF SCIENTIFIC & TECHNOLOGY RESEARCH, 2019)
The blended amine viscosities of N-Methyldiethanolamine and monoethanolamine (MDEA+MEA) are measured for temperature range from 293.15 to 413.15 K. The total amine strength in the solution is maintained at 0.2, 0.3 and 0.4 mass basis. Temperature range 293.15 to 303.15 K is performed with cooling system to achieve the lower stable temperatures during the experiment. Operating pressure is maintained at 1 bar for temperature range 293.15 to 353.15 K and 4.5 bar for higher temperatures. Measured viscosity data is compared with available literature data as well as with modeled data by Grunberg and Nissan model. Earlier viscosity values are available up to 353.15 K for some blended amine concentrations. Therefore, this study is given highly importance for gas absorption process while developing regression models for reacting systems in gas separation. The average absolute deviation between measured viscosity values and viscosity calculated by regression model is around 2.1%. Therefore, measured blended amine viscosities are in good agreement with the predicted viscosity by regression model which is given by Grunberg and Nissan equation.
Keywords: Amines, Dynamic viscosity, Methyldiethanolamine, Monoethanolamine, Temperature effect